2019
DOI: 10.3390/agronomy9050224
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Photosynthetic Photon Flux Density and Root-Zone Temperature for Enhancing Secondary Metabolite Accumulation and Production of Coriander in Plant Factory

Abstract: Coriander is an important aromatic plant, and contains abundant secondary metabolites that are considered to be beneficial for health. The demand for high-quality and fresh coriander in large cities has been growing rapidly. Plant factories are advanced indoor cultivation systems that can produce high-quality plants inside cities with a high productivity. This study aimed to maximize plant growth and the secondary metabolites production of coriander, by regulating photosynthetic photon flux density (PPFD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 40 publications
2
28
0
1
Order By: Relevance
“…Increased shoot dry weight and invariable shoot fresh weight indicated that the water content of the shoot in runner plants was decreased with an increase of light intensity. This agreed with the result of Nguyen et al [34], which reported that the water content in both the stems and leaves of coriander was decreased with an increase of light intensity. The root to shoot ratio of runner plants increased with increasing light intensity ( Figure 6G).…”
Section: Plant Growth and Photon Yield Of Biomass Of Rooted Runner Plsupporting
confidence: 93%
“…Increased shoot dry weight and invariable shoot fresh weight indicated that the water content of the shoot in runner plants was decreased with an increase of light intensity. This agreed with the result of Nguyen et al [34], which reported that the water content in both the stems and leaves of coriander was decreased with an increase of light intensity. The root to shoot ratio of runner plants increased with increasing light intensity ( Figure 6G).…”
Section: Plant Growth and Photon Yield Of Biomass Of Rooted Runner Plsupporting
confidence: 93%
“…Plants cope with oxidative stress by synthesizing antioxidant metabolites, such as flavonoids and phenolic acid compounds [38]. This finding was in agreement with our previous study, which showed that TPC is enhanced under RZTs of 20°C and 30 • C in comparison with 25 • C [19]. In the present research, the TPC and antioxidant capacity of the plants under treatment 15-6 was enhanced while the biomass under this condition did not reduce in comparison with the control treatment.…”
Section: Pigments and Secondary Metabolite Accumulationsupporting
confidence: 93%
“…Measurement of CA and QR contents was conducted using a high-performance liquid chromatography (HPLC) (Shimadzu, Kyoto, Japan) equipped with a mass spectrometry (MS) (Shimadzu, Kyoto, Japan) as described previously [19]. Dried leaves and stems (30 • C, 4 weeks) were chopped and weighted accurately (15.00-15.50 mg).…”
Section: Chlorogenic Acid and Rutin Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the rhythm of these processes can change periodically during a single day. Previous lighting strategies have ignored the effects of photoperiod on circadian rhythm, missing the opportunity to use the circadian rhythm to benefit the growth of crops in PFALs [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%